2018
DOI: 10.1038/s41467-018-07411-7
|View full text |Cite|
|
Sign up to set email alerts
|

Interplay between hypoxia and androgen controls a metabolic switch conferring resistance to androgen/AR-targeted therapy

Abstract: Despite recent advances, the efficacy of androgen/androgen receptor (AR)-targeted therapy remains  limited for many patients with metastatic prostate cancer. This is in part because prostate cancers adaptively switch to the androgen/AR-independent pathway for survival and growth, thereby conferring therapy resistance. Tumor hypoxia is considered as a major cause of treatment resistance. However, the exact mechanism is largely unclear. Here we report that chronic-androgen deprivation therapy (ADT) in the condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 56 publications
2
61
0
Order By: Relevance
“…The finding suggests the signaling pathways act independently and regulate the expression of different subsets of genes. Other studies have reported both positive and negative crosstalk between androgen/AR and hypoxia/HIF1a [26, 28, 29]. Globally there were substantially more AR binding sites than HIF binding sites, demonstrating androgen signaling dominance over HIF signaling in the prostate cancer cells studied.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The finding suggests the signaling pathways act independently and regulate the expression of different subsets of genes. Other studies have reported both positive and negative crosstalk between androgen/AR and hypoxia/HIF1a [26, 28, 29]. Globally there were substantially more AR binding sites than HIF binding sites, demonstrating androgen signaling dominance over HIF signaling in the prostate cancer cells studied.…”
Section: Discussionmentioning
confidence: 70%
“…Hypoxia and HIF have already been implicated in the development and progression of CRPC [24, 25]. Hypoxia was shown to induce AR independence and confer resistance to ADT through a metabolic switch favoring glycolysis [26]. Pseudohypoxia has also been linked to the metabolic switch from oxidative phosphorylation to glycolysis [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia is a typical characteristic of prostate cancer and is a major pathological factor attributing to castration resistance and the metastasis of prostate cancer [1]. When suffering the hypoxic environments, prostate cancer cells regulate a series of gene expression and the corresponding pathways that were essential for cell survival and stress adaptation [2]. Previous researches reported that hypoxia strongly attributed to the poor prognosis and malignancy of prostate cancer [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Crosstalk between the AR and hypoxia/HIF has been reported. ADT in hypoxia promotes adaptive androgen/ AR-independence, and confers resistance to androgen/ AR-targeted therapy [18] . Co-immunoprecipitation assays have confirmed a direct interaction between AR and HIF1a, and ChIP analysis showed HIF1a interacts with the AR on the PSA gene promoter [19].…”
Section: Introductionmentioning
confidence: 99%